Are Australian parents following feeding guidelines that will reduce their child's risk of dental caries?. (14th April 2020) - Martin‐Kerry, Jacqueline; Gussy, Mark; Gold, Lisa; Calache, Hanny; Boak, Rachel; Smith, Michael; de Silva, Andrea
Abstract: Background: Early childhood is an important time to establish eating behaviours and taste preferences, and there is strong evidence of the association between the early introduction of sugar‐sweetened beverages and obesity and dental caries (tooth decay). Dental caries early in life predicts lifetime caries experience, and worldwide expenditure for dental caries is high. Methods: Questionnaire data from the Splash! longitudinal birth cohort study of young children in Victoria, Australia was used to examine beverage consumption and parental feeding behaviours of young children, aiming to provide contemporary dietary data and assess consistency with the Australian dietary guidelines. Results: From 12 months of age, the proportion of children drinking sugar‐sweetened beverages consistently increased with age (e.g. fruit juice consumed by 21.8% at 12 months and 76.7% at 4 years of age). However, the most common beverages for young children are milk and water, consistent with Australian dietary guidelines. In relation to other risk factors for dental caries, at 6 months of age children were sharing utensils, and at 12 months three quarters of carers tasted the child's food before feeding. Conclusions: The increasing consumption of sugar‐sweetened beverages and prevalence of other risk factors for dental caries and obesity through early childhood continues to be a problem despite efforts to raise awareness of these issues with parents.